2018
DOI: 10.1556/030.65.2018.025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antigen conservation and inactivation of gamma-irradiated avian influenza virus subtype H9N2

Abstract: Avian influenza (AI) A subtype H9N2 virus belongs to Orthomyxoviridae family and causes low-pathogenic disease AI. The use of gamma-irradiated viral antigens has been developed in the production of effective vaccines. In this research, LPAIV H9N2 strain, A/Chicken/IRN/Ghazvin/2001, was multiplied on SPF eggs and irradiated by a Nordian gamma cell instrument. Irradiated and non-irradiated AI virus (AIV) samples were titrated by EID50 method and hemagglutinin (HA) antigen was analyzed by HA test as the WHO patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The virus used in our study was AIV sub type H9N2 strain, A/Chicken/IRN/Ghazvin/2001, obtained from the Razi Vaccine and Serum Research Institute of Iran. The optimum dose of gamma irradiated dose and inactivation of virus samples was carried out according to the procedure described by Salehi and coauthors [20]. Briefly; after multiplication of AIV on embryonated SPF (Specific Free Pathogen) chicken eggs, the allantoic fluids were tested using hemagglutination test for Hemagglutinin antigen (HA) titration [20] and virus titration via embryo infective dose (EID50) of infected allantoic fluid was calculated according to the Reed and Muench formula [21,23], Gamma ray dose 30 kGy was recommended for the frozen virus samples [20].…”
Section: Virus and Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus used in our study was AIV sub type H9N2 strain, A/Chicken/IRN/Ghazvin/2001, obtained from the Razi Vaccine and Serum Research Institute of Iran. The optimum dose of gamma irradiated dose and inactivation of virus samples was carried out according to the procedure described by Salehi and coauthors [20]. Briefly; after multiplication of AIV on embryonated SPF (Specific Free Pathogen) chicken eggs, the allantoic fluids were tested using hemagglutination test for Hemagglutinin antigen (HA) titration [20] and virus titration via embryo infective dose (EID50) of infected allantoic fluid was calculated according to the Reed and Muench formula [21,23], Gamma ray dose 30 kGy was recommended for the frozen virus samples [20].…”
Section: Virus and Vaccinesmentioning
confidence: 99%
“…At 48 h post stimulation, supernatants of splenic cells were collected to assess interferon (IFN-gamma and IFNalpha) production using a chicken IFNα Biotek. Inc ELISA (Cat No: DIY0908c-003) and chicken IFNγ-Cytoset ELISA kit, Invitrogen (Cat No: CAC1233) following manufacturer's instructions [20,23]. Also the spleen lymphocyte proliferation assay was carried out with Cell Proliferation ELISA, BrdU kit (colorimetric) Roche Cat.…”
Section: Cytokine Assay and Spleen Lymphocyte Proliferation Responsementioning
confidence: 99%
“…According to positive effects of radiation on biological reagent sterilization and pathogens inactivation, its application for safe vaccines production is increasing. Production of some inactivated vaccines by gamma irradiation such as FMD virus and HSV demonstrated that radiated inactivated viruses retained virus and antigenic structure [16][17][18][19]. Gamma ray is an ionizing radiation which is emitted from the Cobalt-60 isotope and used for virus inactivation without any change in viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Our results contribute to the increasing evidence that the inactivation protocols have to be adapted by virus strain and that many other important factors beyond the concentration of the inactivator itself, such as virus concentration, buffer, incubation time and temperature, have to be considered. Novel inactivation protocols, such as UV and gamma radiation [46] or the use of hydrogen peroxide [13], have already been mentioned in the literature but will need thorough testing and standardization before they can be employed in the context of influenza vaccine production. There are currently new emerging technologies to manufacture influenza vaccines that would not require an inactivation process, such as production of IAV proteins on in vitro cultures or peptides derived from IAV proteins, all showing promising results; yet, egg cultures are currently the cheapest and most efficient way to produce high amounts of vaccines in a relative short amount of time.…”
Section: Discussionmentioning
confidence: 99%